Acknowledgements - Pezzino, Paolo; Focardi, Filippo (Italia Contemporanea - Sezione Open Access, 2021)
It comes as no surprise that a historical institute of the calibre of the Istituto nazionale Ferruccio Parri, which manages a network of 66 local institutes, publishes its own journal. What is less predictable is the fact that, over the years, this journal — ‘Italia contemporanea’ — has managed to become a point of reference within the scholarly debate in Italy, and now hopefully also abroad as we are about to launch this English-language ‘Yearbook’.